An Industrial systems analysis and design on Jolly Plastic Moulding Corporation - Baradas, Jennifer; Cando, Kim.; Sarmiento, Rodeliza; Tappa, Milette (Diliman, Quezon City College of Engineering, 2005)
Jolly Plastic Moulding Corporation is a manufacturer of plastic wares for home and office use. They supply their products, such as plastic drawers, shoe racks, baskets, dish drainers, stands, pails, etc. to department stores, like SM, Landmark, and Gaisano and other marketing distributors like Sunflower Marketing and 1st Excelsior Marketing. Plant visits and interviews with key people in the company were done in order to gather information and document their existing strategies employed by the company. In order to identify and analyze these strategies, strategic management tools were used including the Porter's Five Forces Model, Porter's Generic Strategies, Seven S, and SWOT and TOWS analysis. Through these, it was identified that the company's main strategies include offering their products at a low cost relative to their supplier as well as providing customer satisfaction by mix and matching colors to suit the taste of their customers and offering benchmarked designs of competitors at a lower price. Currently, the company has no stated mission and vision. After a thorough analysis of the company, a vision and mission statements were defined. Its Vision is to be one of the top producers of plastic wares in the country. And in order to achieve this, their Mission is to produce quality products at low cost in order to provide excellent customer satisfaction. These goals may be achieved through a total systems approach. Evaluation and analysis of existing strategies were done with respect to the determined goals of the company derived from the mission statement. A gap analysis was also made to compare if the current strategies employed are aligned toward these goals. From the gap analysis, key strategies were formulated, evaluated, and prioritized using the following set of criteria: ability to address key issues (30%), contribution to cost reduction (30%), ease of implementation (20%) and cost of implementation (20%). Results showed that the top 4 recommended key strategies that must be implemented include reduction in major cost drivers, implementation of a Quality System, improvement in product development and implementation of an Excel/Access-based Information System. From these, operational recommendations were derived. In order to reduce cost drivers a six-month inventory plan and a preventive maintenance program were made. These will help the company reduce its inventory costs by Php 222,158.3175 and maintenance cost by Php 27,893.16 every month. Implementation of the proposed Quality System would ensure that good quality products will be produced and reject rates would be reduced. Besides providing the customers with low cost quality products, other customer satisfaction issue addressed is the response time to customer's requests for specific colors. It is recommended that color charts be used in order to eliminate costly trial and error process of producing desired colors. This will give the company an annual savings of Php 140,000 from elimination of color and trial and will reduce lost sales by around Php 1.6M. The implementation of the proposed Information System would aid in the coordinating operations of the different departments of the company. This maybe a starting point for a more organized inventory system, production planning, as well scheduling of deliveries. Implementation steps and guidelines were provided in order to carry out these recommendations. Through its total systems approach, the company would be able to improve its system and be able to perform better and be able capture bigger market share in the plastic ware industry.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Jolly Plastic Moulding Corporation; Plastics industry and trade; System design